VD_FINDINFO Décision / 2015 / 638 vom 30. Juli 2015 - VD Tribunal cantonal (2015)
FRAIS DE LA PROCÉDURE, PRÉVENU, DÉPENS, CLASSEMENT DE LA PROCÉDURE | 393 al. 1 let. a CPP (CH), 395 let. a CPP (CH), 426 al. 2 CPP (CH), 430 CPP (CH)